Fatty acid profile and antioxidant properties of oils extracted from dabai pulp using supercritical carbon dioxide extraction - Ahmad Jelani, Nur Arina; Azlan, Azrina; Khoo, Hock Eng; Razman, Muhammad Rizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The present work was aimed to optimise the supercritical carbon dioxide extraction of dabai oil from dabai pulp and defatted pulp using RSM in comparison with hexane extraction method. Fatty acid profile and antioxidant properties of the extracted dabai oil were also determined. Optimal RSM conditions were 36 MPa pressure, 40°C temperature and 21 min of extraction time. The extracted yields ranged between 14.13% and 15.42%. Supercritical carbon dioxide extracted oils had lower total phenolics, total flavonoids, and antioxidative activities than the hexane-extracted oils. High-performance liquid chromatography results showed that only vanillic, protocatechuic and gallic acids were identified in both hexane and supercritical carbon dioxide extracted oils of defatted dabai pulp. The total saturated fatty acids were higher in hexane-extracted dabai oil as compared to the supercritical carbon dioxide extracted oil, and vice versa for the unsaturated fatty acid. Although supercritical carbon dioxide extracted dabai oils are inferior to the hexane-extracted oils, they are preferred as they are extracted using green technology.